1995
DOI: 10.1007/bf00409406
|View full text |Cite
|
Sign up to set email alerts
|

Carbon disulphide

Abstract: To evaluate risk factors for coronary heart disease and factors which can influence the course of acute myocardial infarction in workers exposed to CS2 we performed a cross-sectional study of 247 workers in the viscose industry. The control group of 222 men from the same plant was comparable for age, social status and physical work. The CS2 exposure determined by personal air sampling ranged from < 0.2 ppm to 65.7 ppm (median: 4.0 ppm) and the duration of exposure ranged from 4 to 220 (median: 66) months. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The remaining studies in this group [1,6,20,21,22,39] are the strongest methodologically and are nearly consistent in reporting a lack of association between CS 2 and increased blood pressure. These studies also fail to show a consistent positive relationship between exposure to CS 2 and angina, abnormal ECG, CHD prevalence, and serum HDL and LDL cholesterol levels.…”
Section: Chd Risk Indicators and Low Exposure Conclusionmentioning
confidence: 80%
See 3 more Smart Citations
“…The remaining studies in this group [1,6,20,21,22,39] are the strongest methodologically and are nearly consistent in reporting a lack of association between CS 2 and increased blood pressure. These studies also fail to show a consistent positive relationship between exposure to CS 2 and angina, abnormal ECG, CHD prevalence, and serum HDL and LDL cholesterol levels.…”
Section: Chd Risk Indicators and Low Exposure Conclusionmentioning
confidence: 80%
“…A 1995 study by Drexler et al [6] included 247 men of German and Turkish origin who were exposed to CS 2 after 1975, when the German maximum allowable Kotseva Participation rates were 100% for exposed, 46% for unexposed, suggesting selection bias c Exposed group = 5% female, unexposed group=41% female; there is likely to be residual confounding by gender in the multivariable model. That there were 34 participants with abnormal ECG findings indicates the multiple logistic regression model should include maximum of four parameters, but eight parameters were included, suggesting a lack of statistical power d Odds ratio (95% confidence interval) workplace concentration was reduced from 20 ppm to 10 ppm (Table 3).…”
Section: Europementioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that the emission of pollutants into the surroundings can arise from CS 2 used in many ways during the viscose process (6). For humans, carbon disulfide has been described to be a risk factor for many illnesses (58). As a result, it is important to develop new means to decrease the use of this reagent.…”
Section: The Production Of Regenerated Cellulosementioning
confidence: 99%